Proposal to improve the billing process in a service company underthe implementation of the A3 tool - Lenis Freire, Natalia Maria (Ingeniería Solidaria, 2023)
Introduction: This article is a product of the research “Lean Transformation: proposal for improvement to the invoicing process in a service company under the implementation of the A3 tool” developed at the University Santiago de Cali in 2022.Problem: The company under study presented problems with the invoicing indicator because it was estimating revenues but was not issuing the invoice to the client on time, generating problems in the recovery of the money, affecting the cash flow.Objective: To implement the A3 thinking in the invoicing value flow to solve the identified problem.Method: The A3 method was implemented to solve the identified problem, observe the reality, present the facts, propose a logical means to close a gap with respect to the established goal, present a plan of countermeasures and actions, which will later be developed with initiatives and projects of low, medium and high complexity, in the short, medium and long term, and then review the process, verify the results and adjust as necessary.Results: The implementation of the proposed countermeasures achieved that, Bogota went from billing in 21 days, to only 2 days after service delivery.Conclusions: The ability to solve problems in a structured way is nowadays an essential competence of peo-ple in a company that seeks to remain a market leader, from the operational level to process leaders and management.Originality: A3 is a useful tool to reduce the gap between the current state and the future state of a problem.Limitations: Currently there is very little literature and research related to the A3 tool applied to solve problems in the service industry
Keywords: A3 Method; continuous improvement; lean thinking; A3 thinking; PDCA; lean management tool